Algerian society’s response to the coronavirus pandemic - Menasria, Amor (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
In the late of 2019 a new infection disease has identified as new corona virus 19, and in the late of who has declared the infection disease as public health emergency of international concern (PHEIC),since then, the outbreak spread faster around all the world, causing more than 660 million infections, and 6 million of deaths, Algeria, announced its first case of infection on march, 2020, and Algeria com second country in the Africa affected by the pandemic, with more than 271thousand case and 6881deaths. Many studies show that societies are not responding to the pandemic in the same way, many cultural, societal, political factors interference on this responding; thus, the aim of this study is to describe the Algerian responding to the pandemic through four aspects which is; affective, cognitive, organizational, and future effects on the work, education; relationship with family and friends. To collect the relevant data, an online survey was conducted via Google drive, a total of 98 participants were completed the questionnaire, between 06/06/2020 and 22/08/2020, results show that Algerians responding is more realistic and naturalistic in this early period of outbreak, with slight difference about organizational responding, while there are no significant effects on the future of work and education or relationship with family and friends.